MILITARY SERVICE CULTURE AND YOUTH: SOCIO-PHILOSOPHICAL TRANSFORMATIONS IN NEW UZBEKISTAN - Mamajonov, Ibrokhim (Oriental Journal of History, Politics and Law, 2026)
This article explores the socio-philosophical aspects of developing a military service culture among youth and the transformational processes within the context of “New Uzbekistan”. By analyzing the historical paradigms of the Timurid era and the Jadid movement, the study argues that military service acts not merely as a defensive tool, but as a crucial mechanism for social mobility, the formation of national identity, and “intellectual patriotism”. Integrating Ibn Khaldun's concept of Asabiyyah with theories of cognitive security, the research reveals the institutional role of the Armed Forces in integrating youth into modern state-building and civil society.